Association between anxious symptoms and sleeping medication use among US older adults. (29th September 2017) - Harris, Daniel; McNicoll, Lynn; Epstein‐Lubow, Gary; Thomas, Kali S.
Abstract : Objective: To investigate the relationship between anxiety symptoms and sleeping medication use among a nationally representative sample of US older adults. Design: Cross‐sectional design using data from the 2011 National Health and Aging Trends Study to examine the relationship between anxiety symptoms as rated by the Generalized Anxiety Disorder‐2 and self‐reported sleeping medication use. Survey weights were applied to account for complex survey design. Logistic regression was used to measure the association between anxiety symptoms and sleeping medication use after adjusting for sociodemographic factors, physical health, and other sleep‐related issues. Results: In 2011, 13.1% of respondents experienced high anxiety symptoms and 29.0% reported taking a sleeping medication at least once a week during the last 30 days. Results estimate that approximately 4 million US older adults have clinically significant anxiety symptoms and approximately 10 million US older adults used a sleeping medication in the last 30 days. Adjusted results revealed that high anxiety symptoms are significantly associated with sleeping medication use compared to low anxiety symptoms (AOR = 1.57; 95% CI, 1.29‐1.91). Depression symptoms were also associated with sleeping medication (AOR = 1.29; 95% CI, 1.08‐1.55). Conclusions: Results demonstrated that anxiety symptoms are significantly associated with sleeping medication use among US older adults. We also found that depressive symptoms, chronic conditions, and worse self‐rated health are associated with sleeping medication use. As sleeping medications are associated with adverse health events, these results have clinical implications for treating anxiety symptoms among older patients.